2012
DOI: 10.5243/jsswr.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religiousness on Substance-Use Disorder Treatment Outcomes: A Comparison of Black and White Adolescents

Abstract: This study compares 41 Black and 124 White adolescents at intake and discharge from a residential treatment program for substance-use disorders. Study data were obtained as part of a larger study (N = 195) that sought to assess the relationship of helping behavior and addiction recovery. This post-hoc analysis aims to identify cultural strengths that may be associated with recovery from substance-use disorders among Black adolescents. Using regression analyses and controlling for the severity of substance use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…Given the large influences on behavior stated earlier, culture may have an effect on addictive behaviors. Some direct evidences have shown that culture is a factor influencing the use behavior of alcohol ( Zane and Sasao, 2010 ; Krentzman et al, 2012 ) and cigarette ( Benowitz, 1996 ; Florek and Piekoszewski, 2008 ; Coleman-Cowger and Catlin, 2013 ). For example, AA smokers smoke fewer cigarettes per day, metabolize nicotine much lower, prefer mentholated cigarettes and have a higher level of nicotine dependence than Caucasians (CC) smokers ( Benowitz, 1996 ; Coleman-Cowger and Catlin, 2013 ).…”
Section: Cultural Effect In Nicotine and Alcohol Addictionmentioning
confidence: 99%
“…Given the large influences on behavior stated earlier, culture may have an effect on addictive behaviors. Some direct evidences have shown that culture is a factor influencing the use behavior of alcohol ( Zane and Sasao, 2010 ; Krentzman et al, 2012 ) and cigarette ( Benowitz, 1996 ; Florek and Piekoszewski, 2008 ; Coleman-Cowger and Catlin, 2013 ). For example, AA smokers smoke fewer cigarettes per day, metabolize nicotine much lower, prefer mentholated cigarettes and have a higher level of nicotine dependence than Caucasians (CC) smokers ( Benowitz, 1996 ; Coleman-Cowger and Catlin, 2013 ).…”
Section: Cultural Effect In Nicotine and Alcohol Addictionmentioning
confidence: 99%
“…For example, although there are differences in spirituality and religiosity levels between Black and White adolescents receiving treatment for AUD or other SUD, the findings suggested that religiosity was a predictor of 12-step-related behaviors but not of treatment outcomes. 23 In the same study, a significant gender disparity was found in that women were more likely to take the actions outlined in the 12 steps. 23 …”
Section: Special Emphasis Populationsmentioning
confidence: 89%
“… 23 In the same study, a significant gender disparity was found in that women were more likely to take the actions outlined in the 12 steps. 23 …”
Section: Special Emphasis Populationsmentioning
confidence: 89%
“…They found that while lifetime religious practices at intake predicted five of the seven outcome variables (e.g., fewer positive urine toxicology screens during treatment, decreased cravings), God consciousness did not predict any of the outcomes. Using only the Black and White adolescents ( n = 165) from the same sample, Krentzman and colleagues 26 found that baseline religiosity, as measured by the full RBB, predicted 12-step helping and 12-step work during treatment, but had no relation to the likelihood of having a positive urine toxicology screen or to self-reported cravings during treatment. The apparent contradiction between the two studies in the urine toxicology and cravings outcomes underscores the tenuousness of the conclusions that can be drawn.…”
Section: Introductionmentioning
confidence: 99%